Oligonema persimile (Trichiales, Myxomycetes), rediscovered in Brazil after 94 years - Moreira, Izabel Cristina; Cavalcanti, Laise De Holanda; Agra, Leandro De Almeida Neves Nepomuceno; Toschi, Lucca De Araujo; Leonardo-Silva, Lucas; Xavier-Santos, Solange (Phytotaxa, 2025)
Oligonema persimile (Trichiales, Myxomycetes) is a species collected in the Brazilian territory, but with only five records in 94 years. This paper confirms the occurrence of O. persimile in Brazil, and expands current knowledge on its distribution, based on four specimens collected between 2009 and 2023 in two biogeographic domains (Atlantic Forest and Cerrado), in the Northeast and Midwest Regions of the country.